Odpowiedzi

Najlepsza Odpowiedź!
2009-12-07T22:34:58+01:00
(∫5x - 1) (∫5x + 1) + (5x + 1)² - (3x - 2)² = 16x²

(√5)² - 1² + (5x)² + (2*5x*1) + 1² - (3x)² - (2*3x*2) + 2² = 16x²

5 - 1 + 25x² + 10x + 1 - 9x² - 12x + 4 = 16x²

5 - 1 + 25x² + 10x + 1 - 9x² - 12x + 4 - 16x²

-2x + 9 = 0

Pisz zawsze polecenie, bo nie wiadomo jak to obliczać.

-2x = -9 |:(-2)
x = 4,5

:)
2009-12-07T22:36:54+01:00
(∫5x - 1) (∫5x + 1) + (5x + 1)² - (3x - 2)² = 16x²
∫25x+∫5x-∫5x-1+5x²+5*1+1²- 9x²-3x*2-2²=16x²
5x-1+5x²+5+1-9x²-3x*2-4=16x²
5x+1-4x²-3x*2=16x²
5x+1-4x²-6x=16x²
-x+1-4x²=16x²
-x+1=20x²
1=20x²+x
2009-12-07T23:46:37+01:00
W zalączniku ;)
na 100% dobrze
http://img32.imageshack.us/img32/9513/matmad.png